Alarmins and Clinical Outcomes After Major Abdominal Surgery—A Prospective Study. (4th May 2017) - Máca, Jan; Burša, Filip; Ševčík, Pavel; Sklienka, Peter; Burda, Michal; Holub, Michal
ABSTRACT: Purpose : Tissue injury causing immune response is an integral part of surgical procedure. Evaluation of the degree of surgical trauma could help to improve postoperative management and determine the clinical outcomes. Materials and Methods : We analyzed serum levels of alarmins, including S100A5, S100A6, S100A8, S100A9, S100A11, and S100A12; high-mobility group box 1; and heat-shock protein 70, after elective major abdominal surgery ( n = 82). Blood samples were collected for three consecutive days after surgery. The goals were to evaluate the relationships among the serum levels of alarmins and selected surgical characteristics and to test potential of alarmins to predict the clinical outcomes. Results : Significant, positive correlations were found for high-mobility group box 1 with the length of surgery, blood loss, and intraoperative fluid intake for all three days of blood sampling. The protein S100A8 serum levels showed positive correlations with intensive care unit length of stay, 28-day and in-hospital mortality. The protein S100A12 serum levels had significant, positive correlations with intensive care unit length of stay, 28-day mortality, and in-hospital mortality. We did not find significant differences in alarmin levels between cancer and noncancer subjects. Conclusion : The high-mobility group box 1 serum levels reflect the degree of surgical injury, whereas proteins S100A8 and S100A12 might be considered good predictors of major abdominal surgery morbidity and mortality.